A tese das ideias abstratas de David Hume - Melo, Gustavo Oliveira Fernandes (Universidade Federal de São Carlos, 2013)
According to David Hume, the mind is unable to form another kind of idea that is not particular (See: Summary, § 28), ie, it is impossible to form an idea that, at one time, represent many different particular perceptions. When we encounter this thesis, a matter we soon came to mind: as a general term is then formed, ie, how they are formed those words that denote more than one particular perception (perceptions simple or complex)? In order to find an answer to this question, we decided to investigate the structure and genesis of the thesis of abstract ideas in the Treatise of Human Nature, since this is the thesis responsible for forming the general terms. And to achieve this we focus on the genesis of general terms that denote particular qualities. Therefore, we believe that there is a major difficulty for an empiricist conceiving a thesis about the abstract ideas.
Keywords: Percepção (Filosofia); Termo; Linguagem; David Hume; Qualidade particular e a tese das ideias abstratas; Particular quality and the thesis of abstract ideas; CIENCIAS HUMANAS::FILOSOFIA